2010
DOI: 10.1590/s0037-86822010000600003
|View full text |Cite
|
Sign up to set email alerts
|

PCR detection of multiple human herpesvirus DNA in saliva from HIV-infected individuals in Teresina, State of Piauí, Brazil

Abstract: Introduction: Human herpesviruses are frequently associated with orofacial diseases in humans (HSV-1, EBV, CMV and HHV-8), some can also cause systemic disease . The transmission of these viruses occurs by contact with infected secretions, especially saliva. Human immunodeficiency virus infection is associated with an increased risk of HHVs and related diseases. Methods: This work aimed to detect HSV-1, EBV, CMV and HHV-8 DNA in saliva of HIV-infected patients from Teresina, northeast Brazil, by PCR and compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 35 publications
1
13
0
1
Order By: Relevance
“…However, these data do not hold true for all herpes virus family members. Carvalho et al, 28 demonstrated a strong correlation between the presence of EBV and CMV in HIV-seropositive individuals but not between the presence of herpes simplex virus (HSV-1) or human herpes virus type 8 (HHV-8).…”
Section: Resultsmentioning
confidence: 99%
“…However, these data do not hold true for all herpes virus family members. Carvalho et al, 28 demonstrated a strong correlation between the presence of EBV and CMV in HIV-seropositive individuals but not between the presence of herpes simplex virus (HSV-1) or human herpes virus type 8 (HHV-8).…”
Section: Resultsmentioning
confidence: 99%
“…This family of infectious agents is composed of three groups of viruses and has a distinct characteristic of being able to persist in latency and they depend on some stimulus for their reactivation, as occurs in cases of immunosuppression promoted by HIV infection. Herpesviruses have a single double-stranded deoxyribonucleic acid (DNA) molecule in their composition and notably, this group of viruses has been able to infect cells involved in human host [5][6] .…”
Section: Introductionmentioning
confidence: 99%
“…The human herpesvirus 3 (Varicella Zoster Virus -VZV) causes primary varicella, mainly in children and reinfection may be the cause of the herpes zoster (HZ). The human herpesvirus 4 (EBV) is associated with infectious mononucleosis, Burkitt's lymphoma and nasopharyngeal carcinoma [1][2][3][4][5][6] . The human herpes virus 5 (CMV) can cause pneumonia, rhinitis and severe hepatitis, particularly in individuals who have blood transfusions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Entre os principais problemas de saúde pública em todo o mundo, destacam-se às DST e o HIV (Carvalho et al, 2010;Dair, Alonso, Cruz, Barbé, & Garcia, 2014), assim ter uma DST pode aumentar a susceptibilidade à infecção HIV (Corey, Wald, Celum, & Quinn, 2004 Em decorrência das taxas significativas da infecção pelo HIV/AIDS, atualmente, os estudos acerca dos aspectos psicossociais são relevantes para a temática em questão (Casaes, 2007). Dentre eles, destaca-se neste estudo as condutas sexuais de risco, que se configuram em relações sexuais sem o uso do preservativo, possuir múltiplos parceiros sexuais e idade precoce para ter relações sexuais, o que contribui para uma gravidez indesejada e DST, incluindo a infecção pelo HIV (Teva, Bermúdez, Ramiro, & Ramiro -Sánchez, 2013;Araújo, et al, 2014).…”
unclassified